Development and Analysis of an Innovative Precast Concrete U-Shell Beam - Budi Suswanto; Data Iranata; I Gusti Putu Raka; Yanisfa Septiarsilia (IPTEK The Journal of Engineering, 2024)
Precast concrete offers several advantages compared to conventional systems; precast concrete structure technology has become a strategy to enhance standardization, quality control, labor efficiency, and reduce environmental impact and construction pollution. The U-Shell precast beam is a reinforced concrete beam with a 'U' shape designed to enhance practicality and expedite the construction process as it does not require additional formwork and shoring during implementation. The U-Shell beam functions as a permanent formwork, and its design follows either monolithic or conventional methods. In multi-story buildings, using U-Shell beam can increase practical value, reduce costs, and improve time efficiency because they do not require additional formwork and scaffolding in the implementation application. This research involves the development of U-Shell precast beams, structure loading considering various loads, modeling using computer program to determine the structural reactions on each element, reinforcement design for the U-Shell beam structure, and analysis of the lifting and assembly of U-Shell precast beam. The building selected for reviewing U-Shell beams is the Building with a Special Moment Resisting Frame System. From the results of the analysis, the researcher drew several conclusions regarding the reinforcement design for the U-Shell beam under both conditions. In the condition before composite, the number of installed main reinforcements is 6 with a diameter of 13 mm, while in the condition after composite, the number increases to 8 with a diameter of 16 mm. Lifting reinforcement requires a diameter of 10 mm. The difference in reinforcement between before composite and after composite conditions is because before the composite the beam is still receiving self-load, whereas for the after composite condition the change in moment occurs. After all, the beam has received self-load and other loads. The development and analysis of an innovative precast concrete U-Sheel beam has complied with strength and serviceability.